FGF2 crosstalk with Wnt signaling in mediating the anabolic action of PTH on bone formation - Xiao, Liping (Bone Rep, 2018)
The mechanisms of the anabolic effect of parathyroid hormone (PTH) in bone are not fully defined. The bone anabolic effects of PTH require fibroblast growth factor 2 (FGF2) as well as Wnt signaling and FGF2 modulates Wnt signaling in osteoblasts. In vivo PTH administration differentially modulated Wnt signaling in bones of wild type (WT) and in mice that Fgf2 was knocked out (Fgf2KO). PTH increased Wnt10b mRNA and protein in WT but not in KO mice. Wnt antagonist SOST mRNA and protein was significantly higher in KO group. However, PTH decreased Sost mRNA significantly in WT as well as in Fgf2KO mice, but to a lesser extent in Fgf2KO. Dickhopf 2 (DKK2) is critical for osteoblast mineralization. PTH increased Dkk2 mRNA in WT mice but the response was impaired in Fgf2KO mice. PTH significantly increased Lrp5 mRNA and phosphorylation of Lrp6 in WT but the increase was markedly attenuated in Fgf2KO mice. PTH increased β-catenin expression and Wnt/β-catenin transcriptional activity significantly in WT but not in Fgf2KO mice. These data suggest that the impaired bone anabolic response to PTH in Fgf2KO mice is partially mediated by attenuated Wnt signaling.